Nasutoceratops titusi (Ornithischia, Ceratopsidae), a basal centrosaurine ceratopsid from the Kaiparowits Formation, southern Utah. Issue 2 (3rd March 2016) - Lund, Eric K.; Sampson, Scott D.; Loewen, Mark A.
ABSTRACT: The skull and associated postcrania of Nasutoceratops titusi, a basal centrosaurine ceratopsid from the Upper Cretaceous (Campanian) Kaiparowits Formation of Grand Staircase–Escalante National Monument, southern Utah, are herein described. Autapomorphies of this taxon include: an ectonaris that comprises 75% of preorbital skull length; pneumatic nasals; a hyper-robust premaxilla–maxilla contact; a double-faceted, medial flange on the maxilla contributing to the hard palate; and unique supraorbital horncores that are anterolaterally directed, anteriorly curved, torsionally twisted, and relatively enormous. A Bayesian analysis, the first conducted for ceratopsians, is coupled with a parsimony phylogenetic analysis of Centrosaurinae, with both analyses recovering Nasutoceratops as the sister taxon to Avaceratops lammersi from the late Campanian of Montana. Nasutoceratops titusi provides insights into the origins of Centrosaurinae and suggests the existence of a previously unknown clade of short-snouted, long-horned centrosaurines that we here hypothesize to have originated in the southern Western Interior Basin of North America. SUPPLEMENTAL DATA—Supplemental materials are available for this article for free atwww.tandfonline.com/UJVP Citation for this article: Lund, E. K., S. D. Sampson, and M. A. Loewen. 2016. Nasutoceratops titusi (Ornithischia, Ceratopsidae), a basal centrosaurine ceratopsid from the Kaiparowits Formation, southern Utah. Journal of Vertebrate Paleontology. DOI: 10.1080/02724634.2015.1071265.